2016
DOI: 10.1016/j.ceramint.2016.05.148
|View full text |Cite
|
Sign up to set email alerts
|

Improved photoluminescence emission and gas sensor properties of ZnO thin films

Abstract: In this article, we report a comparative study of the influence of pressure-assisted (1.72 MPa) versus ambient pressure thermal annealing on both ZnO thin films treated at 330°C for 32 h. The effects of pressure on the structural, morphological, optical, and gas sensor properties of these thin films were investigated. The results show that partial preferential orientation of the wurtzite-structure ZnO thin films in the [002] or [101] planes is induced based on the thermal annealing conditions used (i.e., pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…The morphologies and optoelectronic properties of ZnO nanostructures and ZnO films are controlled by adjusting their preparation conditions [ 8 27 ]. The crystallinities and morphologies of ZnO-based films have been the focus of many studies [ 9 , 11 , 12 , 15 , 16 , 19 , 21 , 23 25 ], as these properties play important roles in device applications. Most ZnO films, including those grown by PLD [ 12 ], molecular beam epitaxy (MBE) [ 24 ], MOCVD [ 25 ], and MS [ 13 , 21 , 22 ], have shown “particle-like” surface morphologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologies and optoelectronic properties of ZnO nanostructures and ZnO films are controlled by adjusting their preparation conditions [ 8 27 ]. The crystallinities and morphologies of ZnO-based films have been the focus of many studies [ 9 , 11 , 12 , 15 , 16 , 19 , 21 , 23 25 ], as these properties play important roles in device applications. Most ZnO films, including those grown by PLD [ 12 ], molecular beam epitaxy (MBE) [ 24 ], MOCVD [ 25 ], and MS [ 13 , 21 , 22 ], have shown “particle-like” surface morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Banal et al investigated the formation mechanism of this ridge structure in an AlN/sapphire system and found that the AlN ridge structure formed because of the enhanced migration of Al atoms by an alternating source supply [ 30 ]. In addition to the surface structures, the crystallinities and optoelectronic properties of ZnO films have been discussed in several studies [ 9 , 11 , 22 , 29 , 31 33 ], in which, doping, adding buffer layers, and post-annealing have been reported to be beneficial to improve the properties of ZnO films. In this work, we report the formation of ridge-structured ZnO films by designing an extra interfacial layer and tailoring the initial growth conditions in MBE on MgO(111) substrates.…”
Section: Introductionmentioning
confidence: 99%
“…All the 12 diffraction peaks can be associated with ZnO crystals (JCPDS 36-1451) of hexagonal fiber structure, indicating that ZnO crystals have a high purity. 13 The pattern is a vertical contact-separation mode of PENG. The detailed working principle is shown in Figure 3a. When the PENG is pressed, the two friction materials contact.…”
Section: Fabrication Of Piezoelectric Nanogenerator Filmsmentioning
confidence: 99%
“…ZnO는 저렴한 원료, 안정된 화학특성, 간단한 증착방법 등의 장점을 기반으로 광학 및 센서재료로 널리 연구되어 왔다 [1,2]. 또한 ZnO의 넓은 에너지밴드갭(3.3 eV)과 큰 엑시톤 바인딩 에 너지(60 meV)를 이용하여 투명박막트랜지스터 및 단파장 소자로 개발하고자 하는 연구도 광전자 분야에서 진행되고 있다 [3,4].…”
Section: 서 론unclassified